British Thoracic Society survey of the career intentions of respiratory medicine specialty trainees in the UK. Issue 1 (18th May 2022) - Kumar, Kartik; Dave, Kavita; Loewenthal, Lola; Ward, Emily; Addy, Charlotte
Abstract : There were respiratory consultant post vacancies in 82% of surveyed UK hospitals in 2021. Understanding respiratory trainees' career intentions is vital to plan and train a future respiratory workforce. In 2020, the British Thoracic Society surveyed trainee members (n=144) to assess career plans and perceived barriers and facilitators when applying for consultant posts. Most trainees (79, 55.6%) report intending to pursue UK-based posts with general internal medicine responsibilities. Consultant applications are influenced by location, hospital type, previous local experience and availability of subspecialty posts. Insufficient guidance is available regarding consultant applications.